Leveraging Electronic Word of Mouth on TikTok: Somethinc Skin Care Product Innovation to Increase Consumer Purchase Intention - Hasena, Camelia; Sakapurnama, Eko (Faculty of Economics and Business, Hasanuddin University, 2021)
Social Media platform continually assisting industry as a media promoter for its customer. This study aims to determine how the influence of electronic word of mouth on TikTok on purchase intention of Somethinc skincare products through brand image. This study uses a quantitative approach with data collected using a survey method. The research instrument used a questionnaire distributed via google form. The number of samples in this study were 100 respondents who were TikTok users, knew about and had never bought Somethinc skincare products. The analysis technique used in this research is simple linear regression using SPSS version 22 and single test using an online calculator. The results of this study indicate that the four hypotheses of this study are accepted. It was concluded that there was an influence between e-WOM on TikTok on purchase intention of Somethinc skincare products, the influence between e-WOM on TikTok on Somethinc's brand image, the influence between Somethinc brand image on purchase intention of Somethinc skincare product, and influence between Electronic word of mouth on TikTok. towards purchase intention of Somethinc skincare products through brand image.